HIV-1 drug resistance mutations among individuals with low-level viraemia while taking combination ART in Botswana. (1st March 2022) - Bareng, Ontlametse T; Moyo, Sikhulile; Zahralban-Steele, Melissa; Maruapula, Dorcas; Ditlhako, Tsotlhe; Mokaleng, Baitshepi; Mokgethi, Patrick; Choga, Wonderful T; Moraka, Natasha O; Pretorius-Holme, Molly; Mine, Madisa O; Raizes, Elliot; et al.
Abstract: Objectives: To assess whether a single instance of low-level viraemia (LLV) is associated with the presence of drug resistance mutations (DRMs) and predicts subsequent virological failure (VF) in adults receiving ART in 30 communities participating in the Botswana Combination Prevention Project. Methods: A total of 6078 HIV-1 C pol sequences were generated and analysed using the Stanford HIV drug resistance database. LLV was defined as plasma VL = 51–999 copies/mL and VF was defined as plasma VL ≥ 1000 copies/mL. Results: Among 6078 people with HIV (PWH), 4443 (73%) were on ART for at least 6 months. Of the 332 persons on ART with VL > 50 copies/mL, 175 (4%) had VL ≥ 1000 copies/mL and 157 (4%) had LLV at baseline. The prevalence of any DRM was 57 (36%) and 78 (45%) in persons with LLV and VL ≥ 1000 copies/mL, respectively. Major DRMs were found in 31 (20%) with LLV and 53 (30%) with VL ≥ 1000 copies/mL ( P = 0.04). Among the 135 PWH with at least one DRM, 17% had NRTI-, 35% NNRTI-, 6% PI- and 3% INSTI-associated mutations. Among the 3596 participants who were followed up, 1709 (48%) were on ART for ≥6 months at entry and had at least one subsequent VL measurement (median 29 months), 43 (3%) of whom had LLV. The OR of experiencing VF in persons with LLV at entry was 36-fold higher than in the virally suppressed group. Conclusions: A single LLV measurement while on ART strongly predicted the risk of future VF, suggesting the use of VL > 50 copies/mL as an indication for more intensive adherence support with more frequent VL monitoring.